HUBUNGAN EFIKASI DIRI DENGAN TINGKAT KECEMASAN MAHASISWA D3 KEPERAWATAN MENGHADAPI UJIAN AKHIR : THE RELATIONSHIP OF SELF-EFFICIENCY WITH ANXIETY LEVEL OF NURSING D3 STUDENTS FACING THE FINAL EXAMINATION - Indra Ruswadi; Masliha Masliha; Evi Supriatun (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
The final exam, on the one hand makes students happy, especially nursing students, because soon they will be finished through a long period as a student, where students feel free from all duties and obligations, both on campus and when practicing in practice areas (Hospitals, Community Health Centers and Community) , but on the other hand, the existence of this final exam for some students can cause anxiety because they are worried that they will not pass. The purpose of the study was to determine the relationship between self-efficacy and anxiety levels of D3 Nursing students facing the final exam. This type of research is quantitative using a cross-sectional study approach and data analysis using the chi square statistical test. The research population was all final year students of the Polindra D3 Nursing Study Program as many as 42 students and the sample used the total population. The results showed that the chi square statistical test obtained p value 0.000 <0.05, meaning Ho was rejected. Conclusion: there is a significant relationship between Self-Efficacy and Anxiety Levels of D3 Nursing Students Facing Final Exams. Before the final exam, students should increase their self-efficacy by studying with others or increasing their interest in the final exam so as to reduce anxiety.